2023
DOI: 10.5334/jbsr.3232
|View full text |Cite
|
Sign up to set email alerts
|

Primary Necrosis of the Ligamentum Teres Hepatis: A Rare Cause of Acute Abdominal Pain

Abstract: Primary necrosis of the ligamentum teres hepatis (PNLTH) is an extremely rare disease which presents with acute abdominal pain. It has easily been misdiagnosed due to lack of clinical manifestations. Early recognition of PNLTH is crucial for treatment while CT is a good methed to diagnose and differential diagnose PNLTH.Teaching Point: Primary necrosis of the ligamentum teres hepatis (PNLTH) is an extremely rare disease characterized with acute abdominal pain, while computed tomography is the recommended techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Interestingly, the necrosis of the RL is most commonly misdiagnosed with acute cholecystitis [ 4 ]. On clinical level, it was reported that necrosis of the HRL can mimic pancreatitis; for Rui et al showed in 2023 that a patient can present with typical abdominal pain with biological tests in favor of pancreatitis [ 1 , 5 ]. Another report from Tunisia showed that necrosis of the HRL can accompany acute cholecystitis, in which authors opted for cholecystectomy as well as resection of the HRL after confirming the diagnosis per operatively [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the necrosis of the RL is most commonly misdiagnosed with acute cholecystitis [ 4 ]. On clinical level, it was reported that necrosis of the HRL can mimic pancreatitis; for Rui et al showed in 2023 that a patient can present with typical abdominal pain with biological tests in favor of pancreatitis [ 1 , 5 ]. Another report from Tunisia showed that necrosis of the HRL can accompany acute cholecystitis, in which authors opted for cholecystectomy as well as resection of the HRL after confirming the diagnosis per operatively [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hepatic round ligament (HRL)- also called ligamentum teres hepatis, is a remnant of the left umbilical vein atresia [ 1 ]. Anatomically, it starts from the anterior side of the abdominal wall on the right side of the midline and ends at the level of the left portal vein.…”
Section: Introductionmentioning
confidence: 99%